PENGARUH PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS V SDN PENIMPOH - Solatana, Solatana; Gunayas, Ida Bagus Kade; Jaelani, Abdul Kadir; Setiawan, Heri (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2019)
This study aims to determine the effect of Cooperative Script Learning On The Listening Skills of Fifth Grade Students of SDN Penimpoh Kopang district in the academic year 2018/2019. The population of this research is all fifth grade students in SDN Penimpoh Kopang sub-district 2018/2019 school year. Sampling was done by saturated sampling technique, obtained by students of class VA as an experimental class and VB as a control class. In theaxperimental grouplearningusing cooperative script learning methods, whereas in the control group using conventional learning. research instruments in the form of problem questions totaling 15 questions. The result showed that the average value (postest) of the listening of the experimental class students using the cooperative script learning method was 82,6. While the average value (postest) of listening skills of control class students using conventional learning is 74,16. So, there are significant differences between students listening skills using cooperative script learning methods and those using conventional learning. The result of listening skills were analyzed using the polled variance t-test the result of tcount>ttable(1,094>0,683) at a significancelevel of 5%.So it can be concluded that there is an influence of the use of cooperative script learning methods on the listening skills of fifth grade students of SDN Penimpoh Kopang district 2018/2019 school year.